Strategi Kreatif Iklan FWD pada Program Asuransi Bebas Handal di Instagram - Jocelyn Priscilla; Agustrijanto (UNIVERSITAS KALBIS, 2022)
FWD phenomenon issued its newest product, Bebas Handal Insurance. This Advertising has been uploaded on Instagram displays interesting advertising creativity where coffee becomes price of comparison with flat rate. The researcher was interested in researching it because she wanted to find out how the advertising creative strategy used in the FWD ad was Bebas Handal Insurance on Instagram. This research analyzes advertising creative strategy Bebas Handal Insurance on Instagram. This study uses a qualitative approach and uses the post-postivistik paradigm, where researchers see an ad formed by social phenomenon. This study also uses interviews (in depth interviews) to strengthen research. The results of the discussion showed that the advertising creative strategy undertaken by FWD was a message ad by educated, lifestyle and show superior point, where FWD showed its superiority in the form of technology and flat rate.